2019
DOI: 10.3390/molecules24152678
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Review on Pharmaceutical Properties of Gamma-Aminobutyric Acid

Abstract: Gamma-aminobutyric acid (Gaba) is a non-proteinogenic amino acid that is widely present in microorganisms, plants, and vertebrates. So far, Gaba is well known as a main inhibitory neurotransmitter in the central nervous system. Its physiological roles are related to the modulation of synaptic transmission, the promotion of neuronal development and relaxation, and the prevention of sleeplessness and depression. Besides, various pharmaceutical properties of Gaba on non-neuronal peripheral tissues and organs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
168
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(175 citation statements)
references
References 122 publications
(122 reference statements)
2
168
0
5
Order By: Relevance
“…There are two types of GABA receptors, GABA A are GABA-gated chloride channels located in post-synaptic membranes, whereas GABA B are G-protein coupled receptors located both in preand post-synaptic membranes [193]. There are also two sub-types of GABA B , which are called GABA B1 and GABA B2 , and there are GABAa-rho receptors, which form distinct ligand-gated Cl −− channels (previously called GABA C ) [194].…”
Section: The Receptors and Neuromodulatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are two types of GABA receptors, GABA A are GABA-gated chloride channels located in post-synaptic membranes, whereas GABA B are G-protein coupled receptors located both in preand post-synaptic membranes [193]. There are also two sub-types of GABA B , which are called GABA B1 and GABA B2 , and there are GABAa-rho receptors, which form distinct ligand-gated Cl −− channels (previously called GABA C ) [194].…”
Section: The Receptors and Neuromodulatorsmentioning
confidence: 99%
“…GABA is known as an inhibitory neurotransmitter [193]. Studies have shown that GABA has a neuroprotective effect against degeneration, preventing neurotoxic-induced cell death, decreasing apoptosis, and suppressing cytodestructive autophagy [193].…”
Section: The Receptors and Neuromodulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the results also indicated the potential effect of flavonoid on extracellular signal-regulated kinases (ERK), c-Jun Nterminal kinases (JNK), p38, p65, IκBα, IκKα/β phosphorylation, and nuclear factor-kappa B (NF-κB) nuclear translocation(Shen, Lin, Jiang, Wang, & Zhu, 2020). In addition, it has been suggested that GABA has antihypertension, anti-diabetes, anti-cancer, antioxidant, anti-inflammation, anti-microbial, anti-allergy, hepatoprotection, reno-protection, and intestinal protection(Ngo & Vo, 2019). A study in islet β-cells has been revealed that GABA potentially exhibited its antidiabetic effects by modulating on PI3K/Akt-dependent growth and survival pathways.…”
mentioning
confidence: 99%